2021
DOI: 10.1186/s13731-020-00142-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing taxpayers to engage in tax evasion: evidence from Woldia City administration micro, small, and large enterprise taxpayers

Abstract: The main purpose of this paper is to investigate factors that influence taxpayers to engage in tax evasion. The researcher used descriptive and explanatory research design and followed a quantitative research approach. To undertake this study, primary and secondary data has been utilized. From the target population of 4979, by using a stratified and simple random sampling technique, 370 respondents were selected. To verify the data quality, the exploratory factor analysis (EFA) was conducted for each variable … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…SME owners with greater tax knowledge are better able to manage complex tax systems and avoid the additional costs associated with complex reporting duties, and are thus more likely to comply voluntarily. Kassa (2021) discovered that tax parity, tax knowledge, and moral obligation all had a substantial impact on taxpayers' intent to engage in tax evasion. Alabede (2016) finds that a taxpayer's attitude on tax evasion has an impact on compliance behavior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SME owners with greater tax knowledge are better able to manage complex tax systems and avoid the additional costs associated with complex reporting duties, and are thus more likely to comply voluntarily. Kassa (2021) discovered that tax parity, tax knowledge, and moral obligation all had a substantial impact on taxpayers' intent to engage in tax evasion. Alabede (2016) finds that a taxpayer's attitude on tax evasion has an impact on compliance behavior.…”
Section: Resultsmentioning
confidence: 99%
“…According to Tanzania Parliamentary Budget (2020/2021), one of the causes of government budget deficit is non-tax compliance where by estimated tax revenue mismatch with collected tax revenue. Kassa (2021), Ng'eni (2016, Kira (2017) suggested that high tax rates, complicated tax procedures, corruption, high compliance costs and inadequate social services as reasons for noncompliance. Kassa (2021) further argued that tax rates in Africa are so high that they slow down corporate growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tax fraud is a problem for society;therefore, all countries and international organizations are dedicating more and more resources to the fight against tax evasion and fraud, which can cause GDP losses in a country (Kassa, 2021).…”
Section: Fraud and Tax Collectionmentioning
confidence: 99%
“…The tax motivation is understood precisely as the taxpayer's internal willingness to pay taxes. The literature review indicates that tax motivation depends on number of factors including: impact of religion-regardless of the type of religion-and the level of spirituality (Alkhatib et al, 2019;McGee and Benk, 2019;Carsamer and Abbam, 2020;Yuniarta and Purnamawati, 2020;Khalil and Sidani, 2020;Silveus and Stoddard, 2020;Calhoun, 2021;Ishak and Ali, 2021;Kurt and Kurt, 2021;Rahmawati and Dwijayanto, 2021;Wang and Lu, 2021), feeling fairly treated by the tax system and officials (Gerger et al, 2014;Niesiobędzka, 2009), level of knowledge about the operation of tax systems (Kassa, 2021;Kushwah et al, 2021;Newman and Nokhu, 2018;Timothy and Abbas, 2021), tax conscience (Fotiadis and Chatzoglou, 2021), tax discipline (Alm and Torgler, 2006), financial situation (Bejaković and Bezeredi, 2019), trust in public authorities (Alm and Torgler, 2006;Feld and Torgler, 2007;Filippin et al, 2013;Frey and Torgler, 2007), culture (Olaniyi and Akinola, 2020;Alm and Torgler, 2006;Nerre, 2008;D'Attoma, 2018;Feld and Torgler 2007;Feld et al 2008;Kountouris andRemoundou, 2013, after: Horodnic, 2018), gender (Alm and Torgler, 2006;Torgler and Murphy, 2014;Chan et al, 2018;Cyan et al, 2016;…”
Section: Theoretical Aspects Of Entrepreneurs' Tax Incentivesmentioning
confidence: 99%